Nanocarrier-mediated drug delivery systems for spinal cord injury treatment - Cheng, Yajun; Wang, Rui; Zhou, Xiaoyi; Jiang, Hao; Li, Ming; Wei, Xianzhao (Frontiers in Bioengineering and Biotechnology, 2025)
Spinal cord injury is a severe neurological condition that frequently. Results in lasting motor and sensory dysfunction. Traditional drug therapies have shown limited efficacy in addressing the complexities of spinal cord injury. This limitation highlighting the urgent need for innovative treatment strategies. In recent years, nanocarrier-mediated systems have garnered significant attention due to their superior drug delivery capabilities and targeting precision. This review summarizes the latest advancements in the application of nanocarriers for the treatment of spinal cord injuries, discussing various types of nanocarriers, drug loading and capacity and release profiles, as well as targeted delivery strategies. The insights aim to establish a theoretical foundation for future research and clinical applications in this critical area of medicine.